(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A study of the socio-Phycological characteristics and perceived scope conditions is a prerequisite for the suitable design and successful implementation of any project, training, demonstration, or government developmental programs. The present study was conducted to assess the Socio-Psychological Characteristics and perceived scope, constrain of cage culture in reservoir of Telangana, along with the strategies for promotion of cage farming. Most of the respondents exhibited medium level of innovativeness. economic motivation reveal that a majority of the respondents (66.67%) had medium level of economic motivation followed by low (24.67%) and high (8.67%) levels. This implies that majority of fishermen had medium level of economic motivation. farmers had medium and high level of decision-making behaviour. Perception about the cage culture practices in fisheries was measured in terms of their reliability, cost, complexity in operation, usefulness, need and willingness. 52.00% of the respondents perceived the cage culture to be highly reliable. From the findings, it could be concluded that cage culture were perceived to be reliable by a majority of the respondents. more than three-fourths of the respondents (80.00%) perceived the cages to be costly of which 56.00 per cent of the respondents perceived the cost of cages as very high and 24.00 per cent of the respondents perceiving the cost as moderately high. Only one-sixth (12.00%) of the respondents perceived the cost to be affordable. From the findings, it could be concluded that a majority of the respondents perceived the cost of cages to be high. The cage farmers are the key stakeholders of the reservoir fisheries sector. Cage farming is a technology where fishes being enclosed in a net cage which allows free flow water and can be reared fish from fingerling to marketable size. Telangana is the 29th state (formed in 2014) mainly consists of Dams, Reservoirs, Inland tanks, Ponds and Lakes so far, research studies has not been undertaken on Reservoir cage farming in Telangana. Cage culture is an aquaculture production system where fish are held in floating net pens. Cage culture of fish utilizes existing water resources but encloses the fish in a cage or basket which allows water to pass freely between the fish and the pond permitting water exchange and waste removal into the surrounding water.